Metering practice and policy : an examination of battery electromagnetic meter calibration, performance and verification - Thomas, Alun Lewis (Cranfield University, 2009)
The last twenty years has seen the rise to dominance of electromagnetic flowmetering (EFM)technology within the UK water industry network. In the last ten years, the introduction of battery powered EFM designs, for both full bore and insertion meters has seen this technology deployed where before only mechanical meters were used. Nevertheless, despite the increasing use of battery meters, the literature contained little objective reporting of the performance, limitations, calibration or verification of this new technology; in part due to a market monopoly by the original UK developer. This thesis therefore sets out to examine the performance of this battery EFM design both in full bore and probe formats. and to understand the importance of performance differences between it and existing metering: as relevant to the UK regulatory policy and reporting framework and individual water company water balance submissions. Cont/d.